Evolutionary Development Of Distance Banking Services In The Digital Economy - Nozimov Eldor Anvarovich (International Journal on Economics, Finance and Sustainable Development (IJEFSD), 2021)
In the process of transformation of banks in the world, as the provision of banking services on the basis of remote mobile, Internet and other banking technologies, the analysis of current banking technologies and future development of banking technologies is analyzed. The results of this study are of practical importance for the development of remote banking services in the banking system of Uzbekistan